Serverless cloud benchmarking with serverless function traces - Lee, Xuan Hua (Nanyang Technological University, 2024)
With the emergence of cloud computing and popularity of Function-as-a-Service (FaaS) systems, many cloud providers have offered serverless solutions, masking the traditional server complexities. As the implementation of their scheduler and system is not made known to developers, this black-box nature has resulted in the widening information gaps between providers and application developers, who share different Quality of Service goals. This raises questions about performance comparisons across providers.